Pengaruh Kualitas Pelayanan dan Kualitas Produk Terhadap Kepuasan Konsumen di UD. Paon Kembar Desa Peguyangan Kangin Denpasar - Krismantara, Kadek Hary; Suartina, I Wayan; Mahayasa, I Gede Aryana (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The purpose of this study is to find out how the influence of service quality and product quality on consumer satisfaction both partially and simultaneously. The number of samples taken was 91 respondents. The data analysis techniques are validity test, reliability, classical assumption test, multiple linear regression analysis, multiple correlation, t test (t test), determination, and f test (f test). The test results showed that there was a positive and significant influence between the quality of service on customer satisfaction as seen from the t1-count was 5.236 > t-table 1.671 and the sig value of 0.000 so that the first hypothesis was accepted. There is a positive and significant influence between product quality on consumer satisfaction from the t2-count is 3.231 > t-table of 1.671 and the sig value of 0.001 so the second hypothesis is accepted. There is a positive and significant influence between service quality and product quality on consumer satisfaction as seen from the F-count is 31,969 > 3.11 so the third hypothesis is accepted. This research suggestion is expected that UD Paon Kembar always pays attention to the clothes used when working, taking into account the amount of dose given each portion to be able to meet customer needs.